UPAYA PENANGGULANGAN OLEH BANK TERHADAP KREDIT BERMASALAH YANG TIDAK DAPAT DISELESAIKAN PADA MASA PANDEMI COVID - 19 - Bella Novelina, (2022)
The Covid-19 virus pandemic has devastated the Indonesian economy, not only in the Indonesian health sector but also in the economic sector which has also been affected by this pandemic. This pandemic has caused many people to lose their livelihoods. One of them that is very visible is the massive layoffs in several areas of Indonesia, where some people have lost their livelihoods. Of course, Covid-19 directly has an impact on the performance and capacity of bank debtors in fulfilling credit or loan payment obligations. In this case, the government through POJK issued its regulations as regulated in POJK No.11/POJK.03/2020 concerning National Economic Stimulus as a Countercyclical Policy for the Impact of the Spread of Coronavirus Disease 2019 related to rescuing non-performing loans. Based on the explanation above, there are several problems that can be studied as objects of research so that the authors are interested in raising them with the title "Remedial Efforts by Banks Against Non-Resolvable Loans During the Covid-19 Pandemic". This study focuses on regulations governing the rescue of non-performing loans carried out by banks before and during the Covid-19 pandemic and the forms of follow-up carried out by banking institutions when credit rescue cannot be achieved. The method used in this writing is normative juridical research (normative law). This legal research refers to legal norms and principles in reviewing this research.